Influence of Sr doping on structural, electrical and magnetic properties of La0.7Ca0.3MnO3 nanoparticles - Zhao, Shuang; Yue, Xue-Jiao; Liu, Xiang (Ceramics international, 2017)
La0.7Ca0.3MnO3 nanoparticles doped with Sr (La0.7(Ca0.3-xSrx)MnO3, x = 0, 0.05, 0.10, 0.15, 0.20, 0.25, and 0.30) were prepared by sol–gel method. Their structural, electrical and magnetic properties were examined by various analytical methods. XRD (X-ray diffraction) showed a transition in phase from orthorhombic (space group of Pbnm) to rhombohedral (space group of R3̅c) at x = 0.10∼0.15. Cell volume continuously expanded as x increased due to larger radius of Sr2+ ion (1.31Å) compared to that of Ca2+ (1.18Å). This substitution accordingly led to changes in tolerance factor (τ). TEM images confirmed structural phase transition from Pbnm to R3̅c. Average particle sizes of samples with x = 0.05 and 0.25 were measured by TEM as 56nm and 45nm, respectively. Furthermore, a significant increase in Tc and Tp for LCSMO nanoparticles was observed as x rose from lower to higher values. The enhancement of double−exchange (DE) interactions was caused by larger radius of Sr2+ cation, which induced modifications in the Mn−O−Mn bond angles and Mn−O bond distance. This, in turn, boosted magnetic and electrical properties of the resulting nanoparticles. On the other hand, the effect of particle size and intrinsic characteristics was found responsible for approximate values of saturation magnetization. Finally, the increase in coercivity and the decrease in temperature coefficient of resistance (TCR%) were related to spin disordered surface layers of particles and scattering of electrons at grain boundaries, respectively.